Retraction Note: Low prices and high regret: How pricing influences regret at all-you-can-eat buffets (BMC Nutrition. (2015) 1: 36) - (:unkn) unknown (BioMed Central, 2017)
The Editor is retracting this article [1] because concerns have been raised [2] after publication with respect to the analysis of the data reported. The authors have been offered the opportunity to submit a new manuscript for peer review. The authors do not agree with this retraction. © 2017 The Author(s).